MANAGEMENT OF FRIED FISH AT KENAGARIAN SASAK KECAMATAN SASAK RANAH PASISIE KABUPATEN PASAMAN BARAT - -, Mutia - (STKIP PGRI Sumbar, 2014)
This research is purposed to get data or informations and analyze as deepen aboutmanagement of fried fish at Kenagarian Sasak Kecamatan Sasak Ranah Pasisie KabupatenPasaman Barat, from the aspects as follow : 1) stok of basic commodity, 2) teachnique to drying offried fish, 3) marketing of fried fish.Kind of this reseach is qualitative, system approach try to reveal about management offried fish at Kenagarian Sasak Kecamatan Sasak Ranah Pasisie Kabupaten Pasaman Barat,informant be taken with puposive sampling techinique that consist of society who manage the friedfish. And buyer teachnique of analysis data be done with reduction data, presentation data anddraw a conclusion.The result shows that: 1) stock of basic commodity of fried fish at Kenagarian SasakKecamatan Sasak Ranah Pasisie Kabupaten Pasaman Barat be sufficient and quite much. The fishis top commodity for society around. It is need to be keeped the stability so that stock of ish becontinued and it can be depended life for fisherman and manager of fried fish, 2) teachnique andprocess of management fried fish at Kenagarian Sasak Kecamatan Sasak Ranah Pasisie KabupatenPasaman Barat are stilltraditional, still use the simple tools, hand made and be Kecamatan SasakRanah Pasisie Kabupaten Pasaman Barat is the fish that be produced direet send to the collector,most of the fish be carried to the markets around, and most of buyers buy the fish in producitionhome.generally price of fried fish is relative stable and be reached, there are different pricebetween thefried fish be split and the fried fish not be split. depended to the sun in doing process ofdrying, 3) marketing of fried fish at Kenagarian Sasak The fried fish be split has the price moreexpensive. It is because the process of production must be cut in half and need long time.